Perilaku Kekerasan dan Soft Skills: Tinjauan Psikologi Islami dalam Mengembangkan Kesehatan Mental Masyarakat - Thalib, Syamsul Bachri (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2014)
Objective this article explains the psychology of Islamic-based soft skills in tackling violent behavior towards the development of community mental health quality. Violent behavior tends to increase late this requires serious efforts to mitigate them, not only because of adverse abusers, but also carries the risk of harm and harm to others, and society in general. One alternative is to develop soft skills countermeasures based isalami psychology. Soft skills are personal excellence someone associated with the nontechnical things, including the ability to communicate, socialize, and self-control. Soft skills strong influence on one's success and strengthen personalformation are balanced in terms of hard skills, oft skills-based Islamic psychology meaningful self-development oriented image of man in Islam. Conceptually, soft skills has a positive effect in the development of community mental health. Empirically, the results showed that the soft skills that include self-control and emotional maturity, self-concept, interpersonal communication, and social skills, in an effort to raise our influence violent behavior.Keywords: Violent, soft skills, mental healt.